Factors influencing the fire dynamics in open-plan compartments with an exposed timber ceiling. (May 2022) - Nothard, Sam; Lange, David; Hidalgo, Juan P.; Gupta, Vinny; McLaggan, Martyn S.; Wiesner, Felix; Torero, Jose L.
Abstract: Fires in open plan compartments have been the subject of much research over the past decade. This article presents results from an experimental study conducted to explore factors that influence fire dynamics in open-plan compartments with an exposed timber ceiling. A reduced scale testing methodology is proposed and supported by contrasting observed fire behaviour at small scale with large-scale experiments reported in the literature. The reduced-scale experiments highlight the complexity of the fire dynamics. Factors which govern the behaviour include the ignition and self-extinction of the timber; the role that the timber plays in accelerating the transition from Mode 3 (travelling) to Mode 1 (fully developed) behaviour; the ignition and self-extinction of timber which is in a downward facing orientation; the thermal inertia of the ceiling material. Results demonstrate that: different fire modes observed in large scale compartments occur in large scale compartments with combustible timber ceilings; ceiling intrusions influence the fire; and factors that influence the response of timber in open plan compartment fires can, to a large extent, be explained by existing knowledge extracted from bench scale testing and compartment fires with non-combustible linings.